SHARING FINANCING DAN KINERJA BANK SYARIAH - ZAINAB AZIZAH; DENY DWI HARTOMO (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2019)
This study aims to analyze the financing risk and profitability of government and private Islamic banks. This research, data processing is done by using Microsoft Excel 2010 program and testing of each hypothesis is done using the Eviews program. This study aims to find out and analyze the financing risks and profitability of sharia commercial banks. This study uses secondary data that has been processed by certain companies or institutions. The data source used by researchers is accessing financial data on the annual report of the Sharia Bank on the Google website from 2011 to 2017.Analysis of the data used is multiple regression using the panel data method that combines cross section data with time series. The results of the data tested were the higher sharing financing, so that non-performing financing had no significant effect. For the second test, the higher the sharing financing, the profitability of sharia commercial banks will increase, not significantly. The last test the higher the Murabahah financing, the non-performing financing has no significant effect. Therefore, the analysis of financing risk and profitability of Islamic commercial banks is further enhanced so that it can be a monitoring and evaluation for company managers or investors. Keywords : Financing risk, Profitability, non-performing financing, sharing financing, Murabahah.